PANTI SOSIAL LANJUT USIA KOTA AMUNTAI - Noor Rezky Shera; Muhammad Deddy Huzairin (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2026)
The design of the Nursing Home in Amuntai City is motivated by the lack of specialized facilities that support the well-being of the elderly. Elderly individuals require a safe environment with adequate care and support, while others often experience loneliness due to limited social and natural interactions. This study applies a biophilic architectural approach, integrating natural elements to enhance social engagement and improve residents’ quality of life. The findings indicate that incorporating green open spaces and communal areas effectively reduces social isolation and promotes both physical and mental well-being among the elderly.